Konsep Triple Helix Mohammad Natsir Relevansi dan Implementasinya Dalam Pendidikan Da’i di Indonesia - Rizal Firdaus (Rayah Al-Islam, 2020)
This paper aims to find out Mohammad Natsir's triple helix concept and its relevance and implementation in da'i education in Indonesia. The method used is descriptive qualitative, data is taken from literature sources. The results revealed that Mohammad Natsir's trilpe helix concept was to integrate three institutions in the da'i education process, namely masjid (mosque), pesantren, and kampus (university). This concept is considered relevant to the conditions and culture in Indonesia because it has the characteristics of Indonesian culture. This concept is implemented by integrating the curriculum between kampus and pesantren, kampus and masjid. Opportunities for integration between the three institutions are increasingly open with the support of the concept of an merdeka belajar dan kampus merdeka which was proclaimed by the Ministry of Education and Culture of the Republic of Indonesia. The realization of this concept can be in the form of creating joint projects between kampus and masjid by involving students in managing mosques and managing community empowerment programs together. The implementation of the integration of the kampus and pesantrens curriculum can be carried out in the context of the transmission of Islamic knowledge and the education of the da'i character which is very conducive to being carried out in a pesantren atmosphere.